Tax Aggressiveness of Manufacturing Companies Listed on Indonesia Stock Exchange for the 2018-2020 Period - Lilis Kamilah; Ratna Hindria Dyah Pita Sari (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The present study aims to examine and determine the effect of executive compensation, executive Characteristics, and the audit committee on tax aggressiveness (Empirical Study of Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) for 2018-2020 period). The population comprises of 193 manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2020 period with a sample consisting of 47 companies. The samples were selected using purposive sampling with quantitative research technique and panel data. The data were analyzed using a multiple regression technique in STATA 16 version. The measurements of tax aggressiveness include Conforming Tax Avoidance and non-Conforming Tax Avoidance. The results showed that executive Characteristics and executive compensation had a negative impact on tax aggressiveness as measured by conforming tax avoidance. Meanwhile, audit committee had no impact on tax aggressiveness as measured by Conforming Tax Avoidance. Executive compensation had a positive impact on tax aggressiveness as measured by non-conforming tax avoidance, and audit committee had a negative impact on tax aggressiveness. However, executive Characteristics had no impact on tax aggressiveness as measured by Non-Conforming Tax Avoidance.